Design and characterization of biodegradable multi layered electrospun nanofibers for corneal tissue engineering applications. Issue 10 (17th June 2019) - Arabpour, Zohreh; Baradaran‐Rafii, Alireza; Bakhshaiesh, Nasrin L.; Ai, Jafar; Ebrahimi‐Barough, Somayeh; Esmaeili Malekabadi, Hossein; Nazeri, Niloofar; Vaez, Ahmad; Salehi, Majid; Sefat, Farshid; Ostad, Seyed N.
Abstract: Tissue engineering is one of the most promising areas for treatment of various ophthalmic diseases particularly for patients who suffer from limbal stem cell deficiency and this is due to the lack of existence of appropriate matrix for stem cell regeneration. The aim of this research project is to design and fabricate triple layered electrospun nanofibers as a suitable corneal tissue engineering scaffold and the objective is to investigate and perform various in vitro tests to find the most optimum and suitable scaffold for this purpose. Electrospun scaffolds were prepared in three layers. Poly(d, l ‐lactide‐co‐glycolide; PLGA, 50:50) nanofibers were electrospun as outer and inner layers of the scaffold and aligned type I collagen nanofibers were electrospun in the middle layer. Furthermore, the scaffolds were cross‐linked by 1‐ethyl‐3‐(3 dimethylaminopropyl) carbodiimide hydrochloride and glutaraldehyde. Structural, physical, and mechanical properties of scaffolds were investigated by using N2 adsorption/desorption isotherms, Fourier transform infrared spectroscopy, contact angle measurement, tensile test, degradation, shrinkage analysis, and scanning electron microscopy (SEM). In addition, capability to support cell attachment and viability were characterized by SEM, 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assay, and 4′, 6‐diamidino‐2‐phenylindole staining. According to the result of Brunauer–Emmett–Teller analysis, specific surface area of electrospun scaffold was about 23.7 m 2 g ‐1 . Tensile tests on cross‐linked scaffolds represented more suitable hydrophilicity and tensile behavior. In addition, degradation rate analysis indicated that noncross‐linked scaffolds degraded faster than cross‐linked one and cross‐linking led to controlled shrinkage in the scaffold. The SEM analysis depicted nano‐sized fibers in good shape. Also, the in vitro study represented an improved cell attachment and proliferation in the presence of human endometrial stem cells for both cross‐linked and noncross‐linked samples. The current study suggests the possibility of producing an appropriate substrate for successful cornea tissue engineering with a novel design.